Employee Attitude Surveys in the United States - Moore, David (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1956)
SummaryThe Author first discusses generally the employee attitude survey, describing the techniques commonly used, evaluating the ordinary questionnaire technique with its many drawbacks and limitations; these, however, can be — and have been — gradually corrected with time, and one of them has been refined into an instrument called the SRA Employee Inventory. The rest of the article is spent describing and assessing the Inventory, and finally giving the results and trends in employee attitudes which it has yielded.